Fire from heaven : the rise of pentecostal spirituality and the reshaping of religion in the twenty-first century - Cox, Harvey, 1929- (Reading, Mass. : Addison-Wesley Pub., 1995)
"Unlike traditional Protestant and Catholic churches, whose memberships are dwindling, pentecostalism, the most experiential branch of Christianity, has become the fastest-growing form of worship on Earth, and, if present trends continue, could surpass even Catholicism by the turn of the century. From its obscure beginnings a hundred years ago in a tiny black church on Azusa Street in Los Angeles it has grown, especially in the past two decades, to over 410 million people worldwide, becoming the dominant expression of Christian worship in mega-cities throughout the world, from New York and Mexico City to Seoul, Korea. In an effort to understand its extraordinary appeal Harvey Cox has traveled the world to speak and worship with pentecostal congregations on four continents, and he has come to the conclusion that this explosion of spirituality represents a tidal change in what religion itself is and what it means to people."--BOOK JACKET.
Introduction : the little church and the big city -- Millennium coming -- The fire falls in Los Angeles -- The fire spreads -- Another voice : the recovery of primal speech -- Signs and wonders : the recovery of primal piety -- The future present : the recovery of primal hope -- "Your daughters shall prophesy" -- "Music brought me to Jesus" -- "We shall do greater things" : Pentecostalism in Latin America -- Sibyls and Madonnas : reclaiming archaic spirituality in Europe -- Shamans and entrepreneurs : primal spirituality on the Asian rim -- Healers and ecologists : Primal spirituality in black Africa -- Pentecostalism in America : "whose report do you believe?" -- Pentecostalism in America : body snatchers and spiritual warriors -- The liberating Spirit.
Includes bibliographical references (p. 323-332) and index.
Keywords: Pentecostalism -- History; Pfingstbewegung